Is non-high-density lipoprotein associated with metabolic syndrome? A systematic review and meta-analysis - Mardi, Parham; Abdi, Fatemeh; Ehsani, Amir; Seif, Ehsan; Djalalinia, Shirin; Heshmati, Javad; Shahrestanaki, Ehsan; Gorabi, Armita Mahdavi; Qorbani, Mostafa (Frontiers in Endocrinology, 2022)
Introduction: Novel atherogenic lipid indices, including non-high density lipoprotein cholesterol (non-HDL-C) which, is calculated by subtracting the HDL-C value from total cholesterol level. atherogenic index (ratio between Triglycerides (TG) and HDL-C concentrations (TG/HDL-C), and Diff-C (calculated by subtracting low density lipoprotein (LDL-C) from non-HDL-C) have been known as valuable predictors of dyslipidemia and subsequent cardiovascular disease. Previous studies have reported the potential association of novel atherogenic lipid indices with metabolic syndrome (MetS). This meta-analysis aimed to assess the pooled association of novel atherogenic lipid indices with MetS or its components. Methods: A systematic search was conducted through PubMed, Scopus, and Web of Science (WoS) databases from January 2000, until March 2021 to evaluate the association of novel atherogenic lipid indices, including non-HDL-C, atherogenic index, and the difference between non-HDL-C and LDL-C (Diff-C) with MetS. Observational studies were included without any language restriction. As exclusively studies evaluating the association of non-HDL-C with metabolic syndrome (MetS) were eligible to be included in quantitative analysis, random-effect meta-analysis was performed to pool the odds ratios (ORs). A stratified meta-analysis was performed based on the definition of MetS (Adult Treatment Panel (ATP) and International Diabetes Federation (IDF)) and the studied population. Results: Overall, 318 studies were retrieved from an initial systematic search. After screening, eighteen and five studies were included in the qualitative and quantitative synthesis, respectively. Qualitative synthesis revealed an association between non-HDL-C, Diff-C, and atherogenic index with MetS and its components. Stratified meta-analysis showed that increased non-HDL-C level was associated with increased odds of MetS based on ATP criteria (OR: 3.77, 95% CI: 2.14-5.39), IDF criteria (OR: 2.71, 95% CI: 1.98-3.44), in adults (OR: 3.53, 95% CI: 2.29-4.78) and in children (OR: 2.27, 95% CI: 1.65-2.90). Conclusion: Novel atherogenic lipid indices, including atherogenic index, diff-c, and non-HDL-C,are strongly associated with increased odds of MetS and its components. The indices could be considered as potential predictors of MetS and its components in clinical practice.